Laboratory and constitutive analysis of relaxation tests for time-dependent properties of discontinuities. (10th December 2019) - Liu, Ang; Lin, Wenli; Jiang, Jingcai
Highlights: Stress relaxation of discontinuities is induced by viscous deformation and asperity crushing/breakage. The Relaxation Capacity decreases with the increased normal stress or decreased JRC. Asperity crushing/breakage contribute more to the total stress relaxation than viscous deformation. The developed mechanism-based constitutive model well conforms to the testing data. Abstract: Time-dependent behavior of discontinuities is of great significance to understand the long-term stability of rock masses. In this study, a series of shear relaxation tests, in which the initial shear stress was applied to be 85% of the shear strength under corresponding normal stresses, were performed on artificial discontinuities. The relaxation capacity (RC) defined as the ratio of the relaxed stress to the initial shear stress is introduced, and its value is found to decrease with the increase of the normal stress or the decrease of the joint roughness coefficient (JRC). It seems that under a higher normal stress, kinematic behaviors of suppressed dilatancy and asperity crushing/breakage are "competing" with each other to influence the stress relaxation, and the rock mass will not "announce the result" until the comparison and competition of these two behaviors are completed. However, under a larger JRC, asperity crushing/breakage behaviors will increase, which facilitates the shear stress to release. The displacement in normal direction correlating with relaxation behaviors is regarded to be associated with asperity crushing/breakage during relaxation. It might be stated that the total stress relaxation, especially in the rapid relaxation stage, is exclusively contributed by the asperity crushing/breakage behavior, remaining viscous deformation bears a relatively smaller and gradually decreasing contribution during the entire relaxation history. By considering stress relaxation to be induced by viscous deformation and asperity crushing/breakage, a mechanism-based constitutive model, termed as H-K//B, is developed. The good fitting results and the consistency of parameter evolution verify that the developed constitutive relation could accurately capture the time-dependent relaxation behavior of the laboratory results.